The Silence of South African Health Policies on the Language Barrier Between Healthcare Providers and Patients. Issue 3 (1st September 2020) - Sobane, Konosoang; van der Merwe, Chanel; Shandu, Balungile
Abstract: The language barrier continues to compromise adequate healthcare delivery in multilingual healthcare systems. This makes language an important issue for the policy agenda in such systems. This article highlights the silence of selected South African health policies on managing the language barrier in healthcare. The analysis establishes that the selected policies make limited provisions, if any, on the language barrier and fail to account for how the language barrier should be addressed in the provision of care. This silence derives from the level of attention that the subject receives in public discourses and national policies. It is therefore recommended that policies become explicit on how the language barrier in healthcare delivery should be addressed, and that effective implementation as well as monitoring and evaluation mechanisms be put in place to facilitate equitable access to healthcare services for all.